Design, analysis and fabrication of mechanical leaves scraper / Nur Fatihah Saiful Effendy - Saiful Effendy, Nur Fatihah
Mechanical Leaves Scraper is an innovative device inspired by the existing rake where it is widely used by many gardeners or even any people that want to clean up the dried leaves on their home yard. Currently, there are a lot of problems that people need to face when using the rake in order to collect dried leaves. For example, they need to use a lot of energy and will feel back pain when using the rake for such a long time. Thus, by having this device, it will benefit people to easily collect the dried leaves without having worries about their time and other factors that might stop them to clean up their garden as this device is easy to operate and will help people to reduce their energy during the process of collecting the dried leaves.